(3Gdeaghe(B-(3GdCgejI(B-(3GdJMOjGJs - (3fYje EHQGgje(B, (3GdXGgQs ((3YeGf(B:s (3YGde GdcJH GdMOjK(B,s, 2009)
(3eaGgje heOGNd GdESJQGJjLjI hGdEOGQI GdESJQGJjLjI,eQMdI JMdjd GdHjFI,GdJhLg GdESJQGJjLj,GdJfajP GdESJQGJjLj,YedjGJ GdJbhje hGdQbGHI GdESJQGJjLjI,GdHOGFd GdESJQGJjLjI,JMOjGJ GdEOGQI aj GdeSJbHds
(3HHdjhZQGajG(B:(3U U(B.317-328s
Keywords: (3GdEOGQIs